Unequal Training Participation and Training Experience at the Digital Work Place - An Interdisciplinary Study - Gergana Vladova; Philip Wotschack (Proceedings of the Weizenbaum Conference 2019 "Challenges of Digital Inequality - Digital Education, Digital Work, Digital Life", 2019)
Despite technological progress and the resulting changes, the human actor remains the decisive critical factor for the economic success of companies. This paper presents an interdisciplinary approach and research design to examine issues of unequal access to training in the new digital workplace. The research project combines an in-depth state-of-the-art study with an experimental design that tests in a lab environment how learning barriers can be tackled by manipulating the educational situation. In a final step, the methods developed and the results of the experiment are implemented and evaluated in the real situation using the example of one or more companies. The aim of the study is to identify possibilities for different actors in companies to better design working and learning conditions.
Keywords: 330; learning factory; digitalization; training; experiment; low-skilled workers